Strategi Nafkah (Livelihood Strategies) Petani Sawah Tadah Hujan pada Era Pandemi Covid-19 di Desa Kalampadu Kabupaten Ogan Ilir - Yulasteriyani, Yulasteriyani; Randi, Randi; Andriani, Dian Sri; Selian, Sri Nurhayati (Jayapangus Press, 2024)
Each household has a livelihood strategy. The livelihood strategy model carried out is related to the livelihood assets they have, but not all assets can be maximized well in farming household livelihood engineering. Livelihood assets are natural capital, physical capital, financial capital, human capital, and social capital. This study analyses livelihood strategies in the COVID-19 pandemic for rainfed rice farmers in Kalampadu Village, Muara Kuang District, Ogan Ilir Regency. This study will discuss research issues through the theory of livelihood strategies from Herbon and Manig through engineering farmers' livelihood assets. Researchers used descriptive research with a qualitative approach because the issue of rural livelihoods requires farmer subjectivity and in-depth data analysis. Data collection techniques used were participatory observation, in-depth interviews, and literature studies. Researchers use phenomenological research strategies to explore the true meaning of livelihood strategies in identifying social, cultural, economic, and ecological farmers. The results showed that there were seven livelihood strategies for farmer households, namely 1) acquisition strategies, 2) allocation strategies, 3) production strategies, 4) social relation structure, 5) transformation strategies, 6) consumption strategies, and 7) reproduction strategies. The livelihood model of the farmer's household depends on the farmer's livelihood assets that are adaptive to the COVID-19 pandemic.